2x-3y =8......(1)

x+2y =3.......(2)

We will use the elimination method to solve:

First, multiply (2) by -2 and add to (1):

-7y = 2

==> **y= -2/7**

Now substitute y= -2/7 in (2):

x+ 2y= 3

x+ 2(-2/7) = 3

x -4/7= 3

Move -4/7 to the right side:

x= 3+ 4/7

x= 21/7 + 4/7 = 25/7

**x= 25/7**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now